Differences in Time Burden across Local Therapy Strategies for Early-stage Breast Cancer. Issue 11 (November 2021) - Swanick, Cameron W.; Jiang, Jing; Maldonado, J. Alberto; Lei, Xiudong; Shih, Ya-Chen Tina; Caudle, Abigail S.; Baumann, Donald P.; Giordano, Sharon H.; Shaitelman, Simona F.; Shirvani, Shervin M.; Smith, Benjamin D.
Abstract : Background: "Time burden" (time required during treatment) is relevant when choosing a local therapy option for early-stage breast cancer but has not been rigorously studied. We compared the time burden for three common local therapies for breast cancer: (1) lumpectomy plus whole-breast irradiation (Lump+WBI), (2) mastectomy without radiation or reconstruction (Mast alone), and (3) mastectomy without radiation but with reconstruction (Mast+Recon). Methods: Using the MarketScan database, we identified 35, 406 breast cancer patients treated from 2000 to 2011 with these local therapies. We quantified the total time burden as the sum of inpatient days (inpatient-days), outpatient days excluding radiation fractions (outpatient-days), and radiation fractions (radiation-days) in the first two years postdiagnosis. Multivariable regression evaluated the effect of local therapy on inpatient-days and outpatient-days adjusted for patient and treatment covariates. Results: Adjusted mean number of inpatient-days was 1.0 for Lump+WBI, 2.0 for Mast alone, and 3.1 for Mast+Recon ( P < 0.001). Adjusted mean number of outpatient-days was 42.9 for Lump+WBI, 42.2 for Mast alone, and 45.8 for Mast+Recon ( P < 0.001). The mean number of radiation-days for Lump+WBI was 32.4. Compared with Mast+Recon (48.9 days), total adjusted time burden was 4.7 days shorter for Mast alone (44.2 days) and 27.4 days longer for Lump+WBI (76.3 days). However, use of a 15 fraction WBI regimen would reduce the time burden differential between Lump+WBI and Mast+Recon to just 10.0 days. Conclusions: Although Mast+Recon confers the highest inpatient and outpatient time burden, Lump+WBI carries the highest total time burden. Increased use of hypofractionation will reduce the total time burden for Lump+WBI.